1982
DOI: 10.1111/j.1365-2710.1982.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

A Chromatographic Quality Control Procedure Based on HPLC for 5-Hydroxymethylfurfural in Autoclaved D-Glucose Infusion Fluids

Abstract: A specific quantitative chromatographic assay method is described for 5-hydroxymethylfurfuraldehyde (SHMF) in degraded D-glucose solutions incorporating an internal standard. Comparison is made between the chromatographic method and the official direct ultraviolet absorption measurements at 284nm for solutions of D-glucose degraded to different extents. Hospital samples of autoclaved Dextiose Injection, 5% w/v, are also examined by both methods and it is demonstrated that quite different results can be obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Because 5-HMF was used to monitor degradation in glucose samples, a sensitive and accurate assay was required. A reversed-phase HPLC method was developed from published methods (6,7) with some modification. An organic modifier, methanol, was included in the buffered mobile phase, to shorten the retention times and improve column efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because 5-HMF was used to monitor degradation in glucose samples, a sensitive and accurate assay was required. A reversed-phase HPLC method was developed from published methods (6,7) with some modification. An organic modifier, methanol, was included in the buffered mobile phase, to shorten the retention times and improve column efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the recommended U.V. method will also measure intermediates (7) and is to that extent unselective. Using the major absorptivity value of 1316 at 283 nm determined by Taylor (7, S), this would give an equivalent maximum concentration of 23.8 pg/ml of 5-HMF, if the absorbance was due solely to 5-HMF.…”
Section: Methodsmentioning
confidence: 99%
“…glycosylated haemoglobin) 13 . Among the GDPs cited above, 5-HMF and 2-FA are considered as important indicators of degradation 14 , 15 and, according to Linden et al . 3 and Thornalley et al .…”
Section: Introductionmentioning
confidence: 99%
“…Lignocaine hydrochloride 0.3% w/v and laevulose 5% w/v produced as a 500 ml infusion is sterilized by autoclaving at 115-1 18°C for 30 min. Laevulose partially degrades on autoclaving to 5-HMF and related substacces (1,2), which have been reported as a cause of infusion thrombophlebitis (3).…”
Section: Introductionmentioning
confidence: 99%